K-Ar Dating of White Mica from the Lesser Himalaya, Tansen-Pokhara Section, Central Nepal: Implications for the Timing of Metamorphism - Paudel, Lalu P (Nepal Journal of Science and Technology, 2012)
The Lesser Himalaya in central Nepal comprises low- to medium-grade metasedimentary rocks. Metamorphic studies show that they have experienced at least two metamorphic events (M1 and M2). However, exact timing of metamorphism is still controversial. In the present study K-Ar dating of white micas in shales, slates, phyllites, schists and gneisses from the Tansen-Pokhara section was carried out to understand the timing of metamorphism. The muscovite in gneiss from the MCT zone shows an age of about 1255 Ma representing the age of crystallization of parent granite. Detrital mica from the Bhainskati Formation gives an age of about 2441 Ma. Probably this is the age of crystallization of muscovite in its provenance. The recrystallized white micas from slate and phyllite show older ages (Early Paleozoic) in the southern part (279 to 458 Ma). Most probably this represents the timing of M1. Age become gradually younger towards the north due to the mixing of older (M1 related) and younger (M2 related) white micas. Youngest age (10 Ma) was measured from the sample just below the Upper MCT. This age may be related to the M2 which was due to the Late Miocene-Pleistocene reactivation of the Upper MCT. DOI: http://dx.doi.org/10.3126/njst.v12i0.6509 Nepal Journal of Science and Technology 12 (2011) 242-251